EXPERIENCES, CHALLENGES, AND SOLUTIONS OF PHYSICAL EDUCATORS IN ONLINE TEACHING - Jonar T. Martin (Journal of Physical Education)
ABSTRACT The study aimed to determine the lived experiences of physical education teachers in online teaching during the pandemic. This study is qualitative in nature, utilizing phenomenological research design to identify the experiences of physical educators teaching online. The participants in the study consisted of four physical education teachers from two private schools, who are experienced in teaching PE in an online class environment. A semi-structured interview was conducted with an open-ended questionnaire. Transcribing, coding, and thematic analysis were used to analyze the data. From the analysis, themes emerged based on the experiences encountered by PE teachers in teaching online in terms of positive experiences, problems encountered, and solutions taken in dealing with problems or difficulties in online teaching. The findings of the study showed that PE teachers had expressed their lived experiences in teaching PE online, with benefits and problems encountered, as well as solutions and best teaching practices during the COVID-19 pandemic.